The milliped family Striariidae Bollman, 1893. V. Stegostriaria dulcidormus, n. gen., n. sp., Kentrostriaria ohara, n. gen., n. sp., and the convergent evolution of exaggerated metazonital crests (Diplopoda, Chordeumatida, Striarioidea) - Shear, William A.; Marek, Paul E. (Zootaxa, 2022)
Two new genera and species, Stegostriaria dulcidormus (Trisariinae) and Kentrostriaria ohara (Striariinae), are described from Oregon and Idaho, respectively. The new species are distinct from any other striariids, and indeed from any other chordeumatidan millipedes, in having the second dorsal crests greatly enlarged, giving them a fanciful resemblance to stegosaurid dinosaurs. In spite of this similarity, the two species are so distinct they cannot be accommodated in the same genus or the same subfamily. The exaggerated metazonital crests are therefore attributed to convergent evolution. We present a key to the genera of the family Striariidae.